Association Between Midpregnancy Polyunsaturated Fatty Acid Levels and Offspring Autism Spectrum Disorder in a California Population-Based Case-Control Study. Issue 2 (2nd September 2020) - Lyall, Kristen; Windham, Gayle C; Snyder, Nathaniel W; Kuskovsky, Rostislav; Xu, Peining; Bostwick, Anna; Robinson, Lucy; Newschaffer, Craig J
Abstract: Polyunsaturated fatty acids (PUFAs) are critical for brain development and have been linked with neurodevelopmental outcomes. We conducted a population-based case-control study in California to examine the association between PUFAs measured in midpregnancy serum samples and autism spectrum disorder (ASD) in offspring. ASD cases ( n  = 499) were identified through the California Department of Developmental Services and matched to live-birth population controls ( n  = 502) on birth month, year (2010 or 2011), and sex. Logistic regression models were used to examine crude and adjusted associations. In secondary analyses, we examined ASD with and without co-occurring intellectual disability (ID; n  = 67 and n = 432, respectively) and effect modification by sex and ethnicity. No clear patterns emerged, though there was a modest inverse association with the top quartile of linoleic acid level (highest quartile vs. lowest: adjusted odds ratio = 0.74, 95% confidence interval: 0.49, 1.11; P for trend = 0.10). Lower levels of total and ω -3 PUFAs were associated with ASD with ID (lowest decile of total PUFAs vs. deciles 4–7: adjusted odds ratio = 2.78, 95% confidence interval: 1.13, 6.82) but not ASD without ID. We did not observe evidence of effect modification by the factors examined. These findings do not suggest a strong association between midpregnancy PUFA levels and ASD. In further work, researchers should consider associations with ASD with ID and in other time windows.